2015
DOI: 10.1002/cam4.378
|View full text |Cite
|
Sign up to set email alerts
|

Part I: cancer in Sudan—burden, distribution, and trends breast, gynecological, and prostate cancers

Abstract: Despite the growing burden of cancer worldwide, it continues to receive low priority in Africa, across the continent and specifically in Sudan. This is due to political unrest, limited health resources, and other pressing public health issues such as infectious diseases. Lack of awareness about the magnitude of the current and future cancer burden among policy makers play a major role as well. Although, the real scope of cancer in Sudan is not known, the reported cases have increased from 303 in 1967–6303 in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 37 publications
0
49
0
Order By: Relevance
“…Prostate cancer is the leading cancer worldwide and among Sudanese men [1]. Generally cancer of the prostate tends to metastasize to the bone, with less than 1% metastasizing to the maxillofacial region.…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer is the leading cancer worldwide and among Sudanese men [1]. Generally cancer of the prostate tends to metastasize to the bone, with less than 1% metastasizing to the maxillofacial region.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is the commonest cancer in Sudanese women [1]. During pregnancy Tamoxifen and its metabolites affects the rapidly growing fetal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…It forms (30-34%) of all female cancers, 40% are below the age of 45years, i.e. within the reproductive age, this reflects our population pyramid [1].…”
Section: Introductionmentioning
confidence: 94%
“…1 Although, the exact cancer burden and prevalence in Sudan is not known, it is reported that cancer cases have increased from a total of 303 cases in 1967 to 6303 cases in 2010. 2 The burgeoning cancer epidemic in Sudan carries many challenges that are characteristic of developing countries. 3 It is reported that cancer was the third leading cause of death (accounting 5% of total death) after malaria and viral pneumonia.…”
Section: Introductionmentioning
confidence: 99%